Pengaruh Manajemen Bakat Dan Komitmen Organisasi Terhadap Kinerja Pegawai Pada Dinas Koperasi Dan Ukm Provinsi Sumatera Barat - Sumiati, Sumiati; Waruwu , Yoxena (CV. ITTC INDONESIA, 2021)
This study in, human labor is the main key to the company's business success because the performance of an employee is needed in developing a company. Aims to determine the effect of talent management and organizational commitment on employee performance at the cooperative and SME service in West Sumatra Province. The population and the sample are 58 people/employees, using the total sample technique because the total population is less than 100. This study uses primary data in the form of interviews, and direct observation of the research object. Tests using instrument testing, descriptive analysis, classical assumption test, multiple linear regression analysis and hypothesis testing with SPSS 22 program tools. The results of this study are talent management has a positive and significant effect on employee performance and organizational commitment has a negative and insignificant effect on employee performance. at the Department of Cooperatives and SMEs of West Sumatra Province.